ANALYSIS OF NUMERICAL PROCEDURE DISCRETIZATION FLUID FLOW NEAR STAGNATION POINT - ZULKIFTI (NIM : 10108087); Pembimbing : Dr. L. H. Wiryanto, ZICKRY
The local flow behaviour near the singular point is needed to design numerical procedure, which can generate convergen iteration. For that reason, we analyze asymtotic expansion of analytic function z(f) with f = o + iu as potential complex and z = x + iy as fluid domain fluida in cartesius plane. Study results give free boundary leaves solid boundary by forming 1200 certain angle and squared grid is needed to discretazion numeric domain.